Fifth Five Year Plan Proposal Vol. 3. Government of Tripura - Planning Commission (Planning Commission, 1949)
There was practically no Co-operative Organisation in Tripura till 1949. The movement actually started in the First Five Year Plan. Tripura being a land-locked state surrounded by foreign Countries with only a narrow outlet through Assam suffers from many complex problems. Lack of education, communisation difficulties and mixed population with hardly any economic base add to the difficulties of accelerated development of Co-operative Movement. Inspite of these multifarious problems, the Co-operative movement has forged ahead and a basis has been built Up which hoods to be consolidated and strengthened.
Planning and Coordination Department
Government of Tripura Planning and Coordination Department